2017
DOI: 10.1159/000481436
|View full text |Cite
|
Sign up to set email alerts
|

No Association between Vitiligo and Obesity: A Case-Control Study

Abstract: Objective: The purpose of this study was to investigate the relationship between vitiligo and body mass index (BMI) to assess the possible association between vitiligo and obesity. Subjects and Methods: This was a case-control study on a total of 400 participants, i.e., 200 patients with vitiligo and 200 healthy volunteers. Medical assessments were performed by dermatologists using the modified Vitiligo European Task Force form. The height and weight of all of the participants were measured and used to calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…In a study by Dragoni et al , same to ours, vitiligo was revealed not to have any relationship with BMI 18. In contrast, Singh et al reported higher BMI in patients with vitiligo, compared with controls 17.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In a study by Dragoni et al , same to ours, vitiligo was revealed not to have any relationship with BMI 18. In contrast, Singh et al reported higher BMI in patients with vitiligo, compared with controls 17.…”
Section: Discussionsupporting
confidence: 64%
“…3-6 16 17 In a study by Dragoni et al, same to ours, vitiligo was revealed not to have any relationship with BMI. 18 In contrast, Singh et al reported higher BMI in patients with vitiligo, compared with controls. 17 This discrepancy between results might be explained by different mean values of BMI in these studies.…”
Section: Original Researchmentioning
confidence: 92%
“…The creators proposed that in spite of the fact that insulin opposition is expanded in patients with vitiligo, various instruments other than stoutness might be answerable for insulin obstruction in such patients. Besides, Dragoni et al [8] indicated that vitiligo didn't seem, by all accounts, to be related with a high BMI. This absence of an affiliation could be because of a high articulation of p53 and a high centralization of Despite the fact that, stoutness is a proinflammatory condition wherein hypertrophic adipocytes and fat tissueinhabitant cells add to increment circling levels of proinflammatory cytokines [9].…”
Section: Discussionmentioning
confidence: 99%
“…53 A previous study concluded that vitiligo did not have any significant association with higher BMI, although they found a significant association between sudden onset of vitiligo and high BMI. 54 The authors postulated that these results could be explained by the higher expression of p53 (which has a suppressive effect on white adipocyte differentiation, and is thus protective against diet-induced obesity) and the high concentration of transforming growth factor-b (a potent inhibitor of white adipose tissue differentiation). [55][56][57]…”
Section: Vitiligomentioning
confidence: 99%